Peningkatan Kemampuan Guru Kimia dalam Mengembangkan Asesmen Terintegrasi (Konsep, Berpikir HOTs, Teknologi) pada Materi Termodinamika I - Florida Doloksaribu; Raidil (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The purpose of this study is to improve the ability of chemistry teachers in understanding integrated assessments. The study used a mixed method Embedded Design Experimental. The ability of chemistry teachers to design and implement integrated assessments with innovative learning models, problem-solving thinking skills, and technological skills is still a challenge, especially abstract materials such as the laws of Thermodynamics (energy and its changes). Previously, observations were conducted based on questionnaires distributed to participants to determine the level of understanding of participants in making integrated assessments. Participants' responses to ignorance on integrated assessments reached 80%. Therefore, the MER approach was carried out to improve the quality of knowledge on integrated assessments. Based on the results of the implementation, the average N-gain was in the medium and high categories (conceptual understanding 0.69, problem-solving thinking skills 0.62, and PhET skills 0.71), this indicates an increase in quality. Through the ANOVA test, the acquisition of conceptual understanding scores with (p <0.001) showed a significant difference in participants who obtained the medium and high categories. Meanwhile, there were no significant differences in problem-solving thinking skills (p = 0.024) and PhET technology skills (p = 0.071) across all participants. This study involved 20 chemistry teachers from Maluku and Papua. Participants' responses to the assessment implementation were 80% good and 20% very good.